A new actinopterygian fish species from the Late Permian Beaufort Group, South Africa - Bender, Patrick (Bernard Price Institute for Palaeontological Research, 2001)
A new genus and species of actinopterygian (ray-finned) fish, Bethesdaichthys kitchingi, is described from the Tatarian, Late Permian, Lower Beaufort Group of South Africa. Bethesdaichthys is presently known from three localities, two in the New Bethesda and one in the Victoria West districts of the Karoo region respectively. The fossils were recovered from within the Abrahamskraal Formation Tapinocephalus Assemblage Zone at the Victoria West locality, and from an uncertain Formation possibly closely equivalent to the Balfour Formation, within the Dicynodon Assemblage Zone at the New Bethesda sites. Bethesdaichthys kitchingi is a fusiform fish, up to approximately 300mm in total length, with the skull displaying a moderately oblique suspensorium, and a maxilla with a large sub-rectangular postorbital blade. Furthermore there is a complex of four suborbital bones adjacent to the orbit. The pectoral fin is large relative to body size and the tail is heterocercal with an elongate tapered dorsal body lobe. The anterior midflank scales in particular exhibit a distinctive dermal ornamentation consisting of numerous ganoine ridges. The phylogenetics and interrelationships of Bethesdaichthys kitchingiare examined. It appears to exhibit a relatively conservative morphology similar to that found in possibly related Carboniferous taxa such as the South African taxa Australichthys and Willomorichthys. Bethesdaichthys kitchingiis derived relative to stem-actinopterans such as the Howqualepis and Mimia, and also derived relative to southern African Palaeozoic actinoptyerygians such as Mentzichthys jubbi; and Namaichthys schroeden; but basal to stemneopterygians such as Australosomus, Perleldus and Saurichthys.
Keywords: Bethesdaichthys; Palaeoniscid; Late Permian; Tatarian; Beaufort Group; Actinopterygii